Effects of different additives on fermentation quality, mycotoxin concentrations, and microbial communities in high-moisture corn kernels during wet storage - Wang, Xingya; Sun, Linlin; Zhang, Shoumei; Guo, Yuqiu; Chen, Lirong; Gong, Kuijie; Liu, Kaichang (Frontiers in Microbiology, 2024)
IntroductionThe moisture content of corn kernels at harvest in China is relatively high, and wet storage effectively preserves high-moisture corn kernels. However, ensuring effective fermentation during storage is crucial.MethodsTo address this, we systematically investigated the variations in fermentation quality, mycotoxin concentrations, and microbial community composition under different additive treatments. The treatments included CK (control, deionized water), LAB homo- and hetero-lactic acid bacteria: Lactiplantibacillus plantarum and Weissella confusa MF01, and EN (cellulase), followed by 60 and 90 days of fermentation.ResultsThe results indicated that both LAB and EN treatments significantly reduced the concentrations of deoxynivalenol (DON), aflatoxin B1 (AFB1), and zearalenone (ZEN) compared to CK during the wet storage of high-moisture corn kernels. LAB treatment notably increased lactic and acetic acid levels, decreased pH and NH3-N content, and improved crude protein (CP, 8.24% DM) and starch content (73.01% DM) compared to CK. LAB treatment also reduced water-soluble carbohydrate (WSC) content (5.05% DM). Microbial diversity was reduced in the LAB treatment, as evidenced by decreases in both common and unique operational taxonomic units, while the relative abundance of Weissella increased after 60 days compared to CK. In contrast, despite higher lactic and acetic acid levels in the EN treatment, the pH did not decrease significantly due to higher NH3-N content. Overall, the LAB treatment outperformed other treatments by achieving lower mycotoxin concentrations, better fermentation quality, and superior preservation of nutritional components.DiscussionThis study provides valuable theoretical support and practical guidance for improving the wet storage of high-moisture corn kernels and enhancing their safety and nutritional value during storage.